CHARTING THE COURSE: EXPLORING THE FUTURE OF ONLINE EDUCATION MANAGEMENT AND EFFICIENCY IN MAURITIUS' SECONDARY SCHOOLS - Gunnoo, Leenshya (PEOPLE: International Journal of Social Sciences, 2024)
This conceptual study examines the challenges faced by secondary school educators in Mauritius in adopting online classrooms, particularly after COVID-19. It evaluates online education as a tool for enhancing education quality, focusing on gender, ICT infrastructure, and educators' technological and pedagogical knowledge. Through qualitative research, specifically in-depth interviews, the study explores educators' experiences and perceptions. The conceptual analysis suggests that gender may influence educators' attitudes toward technology, with female educators potentially facing more challenges. The availability of robust ICT infrastructure and technical support is crucial for educators' readiness to adopt online teaching. Additionally, educators' knowledge of technology and its pedagogical use is key to successfully integrating online learning. These conceptual insights are intended to guide future research and policy decisions, highlighting the need for targeted professional development and strategic investments in ICT to support online education adoption in Mauritius. Future research should include empirical data and expand to other regions and educational levels for a broader understanding of online education adoption.